Impacting Environmental and Public Health through the Use of Dual Targeted and Tailored Asthma Educational Interventions. (9th July 2015) - Carrillo, Genny; Han, Daikwon; Lucio, Rose L.; Seol, Yoon-Ho; Chong-Menard, Betty; Smith, Kenneth
Abstract : Home-based asthma environmental education for parents of asthmatic children is needed since many health professionals lack the time to offer it. However, developing targeted and tailored education is important in order to address the individual needs of participants. This nonrandomized longitudinal study examined knowledge on asthma with an Asthma and Healthy Homes educational intervention training offered to parents of children from low income families who reside in the Rio Grande Valley of Texas. Eighty-nine parents received the training and pre- and posttest surveys were used to measure knowledge outcomes. A standardized assessment on asthma triggers was used to identify the different triggers each child was exposed to, and a follow-up survey was conducted 6 months after the educational intervention to identify how many parents reported household and behavior changes as a result of the training. Results showed significant changes in behavior by participants as a result of the training received. This study suggests that these behavioral changes are attributed to the dual "targeted" and "tailored" educational interventions delivered to parents which resulted in a greater understanding of how to manage asthma by eliminating asthma triggers in their respective homes.